The Effect of Anti-Semitism legislations on freedom of speech in the USA - ضيف, مسعي, بلقاسم وليد الجموعي (University of El-oued, 2022)
كحوصلة للدراسة قمنا بتغطية نتائج او اثار تشريعات مضادات السامية . والبحث في العلاقة المثيرة للجدل بين تشريعات معاداة السامية وحرية التعبير. أسست أمريكا صعودها الكبير كدولة تمثل الديمقراطية الحديثة من خلال الحماية الهائلة للحقوق الدستورية، والتي شكلت تفردها وجعلتها موطنًا لأرض الحرية. من بين هذه الحقوق حرية التعبير، والتي لم تثبت فقط أنها أساسية، ولكنها أيضًا رفاهية أساسية يتمتع بها الأمريكيون والتي تجعلهم يتأكدون من أن أصواتهم مسموعة وأن حكومتهم تخضع للمراقبة. ومع ذلك، فإن أمريكا معروفة أيضًا بالعديد من الظواهر التي تنبع من وجهات النظر الثقافية والعرقية والدينية والعرقية المتحيزة. وبالتالي ، ومن أجل حماية أمن الأمة وشعبها على الرغم من خلفياتهم المختلفة ، اضطرت الولايات المتحدة إلى تقديم تعويضات أدت إلى الحد من مجمل بعض الحقوق الأساسية مثل حرية التعبير. إحدى هذه الظواهر هي حقيقة معاداة السامية ، كانت معاداة السامية أحد الأسباب الرئيسية التي أدت إلى إجراء تعديلات على حرية التعبير في الولايات المتحدة وفرض بعض القيود بطريقة يعتقد أنها تحمي المجتمع الأمريكي من خطاب الكراهية. ومع ذلك، فإن هذه القيود التي تأثرت بمعاداة السامية كان لها العديد من الآثار على حرية التعبير في الولايات المتحدة. As a final thought in this dissertation we uncovered the consequences Anti-Semitism legislations as well as manage the contentious interplay between Anti-Semitism legislation and free speech. America's major emergence as a country that epitomizes modern democracy was formed by the widespread preservation of constitutional rights, which gave it a distinct identity and earned it the moniker "land of freedom." Freedom of speech is one of these rights, which has shown to be not only basic, but also a necessary luxury for Americans, allowing people to ensure that their views are heard and their government is held accountable. However, America is also notorious for a slew of phenomena stemming from cultural, ethnic, religious, and racial prejudices. As a result, in order to safeguard the nation's and people's security, the United States was compelled to make compensations, which resulted in the totality of some core rights, such as freedom of speech, being limited. Anti-Semitism is one of these phenomena. In reality, anti-Semitism was one of the key causes that led to changes in freedom of speech in the United States and the imposition of various limits in order to protect American society from hate speech. However, anti-Semitism-influenced restrictions had a significant impact on freedom of speech in the United States.
Keywords: حرية التعبير ، حق دستوري ، معاداة السامية ، التشريعات الأمريكية; Anti-Semitism, Anti-Semitism Legislations, Constitutional right, Freedom of Speech.